Searching for New Objects with the B[e] Phenomenon - Aisha Zh. Naurzbayeva; Nazgul Sh. Alimgazinova; Anatoly S. Miroshnichenko; Corinne Rossi; Inna V. Reva; Raushan I. Kokumbayeva; Chingis T. Omarov; Sergei V. Zharikov; Nadine Manset; Ashish Raj; Arti Joshi; Richard J. Rudy; et al. (Galaxies)
Objects with the B[e] phenomenon, whose defining features are the presence of forbidden emission lines and infrared excess coming from circumstellar dust, represent a broad range of evolutionary stages from pre-main-sequence to planetary nebulae. They are important for understanding mechanisms of the circumstellar matter formation and evolution. However, it is not easy to discover them, especially among faint stars, as forbidden emission lines are usually weak and hardly noticeable in low-resolution spectra. We developed photometric criteria to search for candidate objects with this phenomenon based on a combination of optical and near-infrared color indices and found nearly 40 objects that satisfy these criteria. Spectroscopy of the candidates allows us to make more confident conclusions on their classification. We present the results of our photometric and spectroscopic observations of six objects, which are part of a large list of ∼40 objects that satisfy our photometric selection criteria for candidate objects with the B[e] phenomenon. Forbidden lines of neutral oxygen were clearly detected in the optical spectrum of one object (VES 683) and suspected in three others. One object, AS 415, is most likely a binary system with components that exhibit partial eclipses but without the B[e] phenomenon, while IRAS 20402 + 4638 may be a luminous member of the FS CMa objects group.